Formalin-free tissue embedding is less hazardous and results in better DNA quality. - Maarten Niemantsverdriet; Ageeth Knol; Jose van der Starre-Gaal; Agnes Marije Hoogland (PLoS ONE)
Disease diagnosis, prognosis, and therapy choice progressively rely on good-quality Deoxyribonucleic acid (DNA) for molecular analysis. As tissue processing is routinely performed worldwide with ancient techniques using toxic and DNA-damaging formaldehyde, the quality of DNA isolated from embedded tissues used for diagnostics is poor. We used a novel formalin-free tissue embedding method to process tissues and show that, after 5 years, DNA quality is superior to formalin fixation.